PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT FASILITATOR AND EXPLAINING TERHADAP PENALARAN MATEMATIKA DAN KEPERCAYAN DIRI SISWA - Ayu Waningsih (Jurnal Riset Pembelajaran Matematika, 2020)
The problem in this study is the low level of mathematical reasoning and students' self-confidence. Lack of student reasoning can be seen from the students' pretest scores, where out of 20 students only 8 students achieved above average scores and 12 other students scored below the average, so about 60% of students scored below average. Seeing these problems, the authors are interested in applying the Student Facilitator And Explaining learning model where students can be involved to be more active in the teaching and learning process. The purpose of this study was to determine whether there was an effect of the cooperative learning model type student facilitator and explaining on mathematical reasoning and student self-confidence. Hypothesis testing used MANOVA analysis (Multivariate Analysis of Variance) with a significant level of 0.05 from the data obtained a significant value of 0.000 where 0.000 <0.05 and according to the criteria that H0 is rejected and H1 is accepted, there is a positive influence on the Student Facilitator and Explaining learning model on Mathematical Reasoning and Student Confidence. So it can be concluded that (1) Judging from the SPSS Descriptive Statistics output, the posttest scores of Reasoning and Student Confidence using the Student Facilitator And Explaining learning model are included in the high category. (2) Results of the MANOVA (Multivariate Analysis Of Variance) test with significant treatment by the Pillai's Trace, Wilks Lambda, Hotelling's Trace, Roy's Largest Root procedures. Obtained a significant value of 0,000 where 0,000 <0.05 and according to the criteria that H0 is rejected and H1 is accepted, there is a positive influence on the Student Facilitator and Explaining learning model on Mathematical Reasoning and Student Confidence.An abstranct is a brief summary of a research article, review, or any-depth analysis of a particular subject or disipline, and is often used to help the reader quickly ascertain the paper purposes. When used, an abstract always appears at the beginning of a manuscript or typescript, acting as the point-of-entry for any given academic paper or patent application.